Clonogenic multipotent stem cells in human adipose tissue differentiate into functional smooth muscle cells - Rodríguez, Larissa V; Alfonso, Zeni; Zhang, Rong; Leung, Joanne; Wu, Benjamin; Ignarro, Louis J (Proceedings of the National Academy of Sciences - PNAS, 2006)
Smooth muscle is a major component of human tissues and is essential for the normal function of a multitude of organs including the intestine, urinary tract and the vascular system. The use of stem cells for cell-based tissue engineering and regeneration strategies represents a promising alternative for smooth muscle repair. For such strategies to succeed, a reliable source of smooth muscle precursor cells must be identified. Adipose tissue provides an abundant source of multipotent cells. In this study, the capacity of processed lipoaspirate (PLA) and adipose-derived stem cells to differentiate into phenotypic and functional smooth muscle cells was evaluated. To induce differentiation, PLA cells were cultured in smooth muscle differentiation medium. Smooth muscle differentiation of PLA cells induced genetic expression of all smooth muscle markers and further confirmed by increased protein expression of smooth muscle cell-specific alpha actin (ASMA), calponin, caldesmon, SM22, myosin heavy chain (MHC), and smoothelin. Clonal studies of adipose derived multipotent cells demonstrated differentiation of these cells into smooth muscle cells in addition to trilineage differentiation capacity. Importantly, smooth muscle-differentiated cells, but not their precursors, exhibit the functional ability to contract and relax in direct response to pharmacologic agents. In conclusion, adipose-derived cells have the potential to differentiate into functional smooth muscle cells and, thus, adipose tissue can be a useful source of cells for treatment of injured tissues where smooth muscle plays an important role.